A SUCCESSFUL DOWNSTAGING OF AN IRRESECTABLE DUODENAL ADENOCARCINOMA TO A SUCCESSFUL WHIPPLE’S PROCEDURE, NEVER LOSE HOPE: A CASE REPORT - Qubtia, Maria; Farooqi, Amer Rehman; Khan, Sarah; Kabir, Syed Irfan; Mahmood, Tariq; Ilyas, Hajira (Journal of Ayub Medical College Abbottabad, 2024)
Small bowel cancer is a rare cancer that contributes to less than 5% of all gastrointestinal cancers. Whereas primary duodenal adenocarcinomas account for approximately 50% of all small bowel cancers. The annual incidence rate worldwide is less than 1 case per 100,000. The median age of presentation is 67 years. There is no gender predilection. The common histological types include adenocarcinoma, neuroendocrine tumour, Gastrointestinal stromal tumour, and lymphoma.